Renewed Quality for Cultural Cities: A New Approach to Manage the Tourist Area of Puri Saren Ubud in Times of Covid-19 - I Gede Wyana Lokantara; Farisa Maulinam Amo (Centre For Tourism Planning and Development, 2022)
Puri Saren Ubud is one of the heritage tourist areas as well as the residence of the king and his family who hold the government. The tourist area is one of the attractive destinations for tourists to visit. The Covid-19 pandemic has had a major impact on tourist visits to Bali, including to Puri Saren Ubud, whose numbers are decreasing and impacting the economic income of the surrounding community. Puri Saren Ubud based on its spatial typology uses the concept of traditional Balinese architecture which consists of three spatial functions, namely macro, micro and meso rooms and has met room standards for operationalizing tourism activities during the Covid-19 pandemic. Analysis of respondents perceptions regarding the existence of a new approach in the pattern of travel activities, including space restrictions to carry out social distancing by providing a space separator symbol, reaching a score of 85.67% as an effort to prevent crowds of visitors that can trigger the spread of the Covid-19 virus. Perceptions of changing the tourism model with the concept of virtual cultural performances scored 57.00%, they argue that cultural performances are better witnessed directly because they are related to the cultural values ​​contained in the performing arts but still prioritize health protocols